An Open Resource for Non-Human Primate Optogenetics - Tremblay, Sébastien (Neuron, 2020)
Optogenetics has revolutionized neuroscience in small laboratory animals, but its impact on animal models more closely related to humans, such as non-human primates (NHP), has been mixed. To make evidence-based decisions in primate optogenetics, the scientific community would benefit from a centralized database listing all attempts, successful and unsuccessful, at using optogenetics in the primate brain. We contacted members of the community to ask for their contribution to an open science initiative. As of this writing, 45 laboratories around the world contributed more than 1000 injection experiments, including precise details about their methods and outcomes. Of those entries, more than half had not been published. The resource is free for everyone to consult, and to contribute to, on the Open Science Framework website. Here we review some of the insights from this initial release of the database and discuss methodological considerations to improve the success of optogenetic experiments in NHP.